Paradigmen Personaler Identität Band I: Paradigmen und Medialität der Geschichtsschreibung - Grenzmann, Ludger 1939-2017 (Abhandlungen der Akademie der Wissenschaften zu Göttingen. Neue Folge, 2016)
The Neuen Abhandlungen der Akademie der Wissenschaften zu Göttingen are the most important publication produced by the Göttingen Academy and follow a long and splendid tradition. From 1752 to 1842 the "Königliche Gesellschaft der Wissenschaften", as the Academy was then known, produced its Latin Commentarii and Commentationes, in which such reknowned scholars as Haller, Gesner, Blumenbach, Heyne and Gauß presented their work. Since 1842 the Academy has published the Abhandlungen in German, containing the results of work by members of the Academy, staff in the Academy's research projects and invited scholars. The publications are the product of a lecture and ensuing discussion at the Academy. On the whole the Neuen Abhandlungen will, just as its precessor the Abhandlungen , contain contributions from the entire field of the humanities.